The accuracy of currently used WHO´s Body Mass Index cut-off points to measure Overweight and Obesity in Syrian women: A correlation study - Mohammed A Bakir; Mahfouz M Al-Bachir; Kholoud B Hammad; Khuzama M Habil; Husam H Ahmad (Epidemiology, Biostatistics and Public Health)
Purpose: Obesity is a common health problem in both developed and developing countries. BMI is commonly used to identify obesity. However, there is increasing evidence that the relationship between BMI and BF% differs among various ethnicities. The main objectives of this study are (1) to evaluate the correlation between BF% as determined by BIA, DEXA, Deuterium oxide (D2O) and BMI, (2) to assess the accuracy of currently used WHOÅLs BMI cut-off points to identify overweight and obesity among Syrian women.